AN EXPOSITION OF BERKELEY’S ABSTRACT THEORY - Akpa, Matthew Ikechukwu (EBSU Journal of Social Sciences and Humanities, 2024)
The concept of abstraction as developed by Plato received a well-treated exposition during the era of George Berkeley. In his attempt to distinguish himself from the empiricist theory of John Locke, Berkeley stated that nothing exists without been first formed by the ideas. The existence of all things is a fulfillment of minded conceived ideas and nothing can ever be without first received by the mind through its ideological conception. However, the researcher affirmed the position of George Berkeley stating that all things are as a result of the mind and whatever exist or whatever name given to a thing is based on how such appears to an individual. The concept of abstraction is individualistic as nothing receives a general notion or treatment. Whatever a name given to a thing is as a result of whatever and however such appears to mind. However, nothing exists without been abstracted from the mind as the mind is the foundational block of all things.